Missio Dei through complexity theory: Complexity to total salvation - Jonas S. Thinane (In die Skriflig, 2022)
Complexity theory continues to fascinate the academics owing to its capability to describe complex systems holistically. This theory makes it possible to understand a complex system by studying its constituent subsystems. Understanding the missio Dei has become somewhat complex, particularly from the perspective of the 1952 Willingen Conference. This conference emphasised mission as a divine activity embodied in the core missions of the Son (missio Christos) and the Holy Spirit (missio Spiritus). It highlighted that the triune God, and not the church, is the source and centre of the missio Dei. Conversely, missio hominum and missio ecclesiae denote the commissions of human participation in the mission of the triune God. Observably, the complex interaction of these core missions and commissions aimed at attaining salvation as the main objective of the missio Dei. This arguably warrants innovative research to explore the missio Dei as a rather complex phenomenon. Correspondingly, as there seems to be no direct complexity-theoretic study of the missio Dei, this article analyses the literature to propose a complexity-theoretic analysis of the missio Dei. Further research is therefore warranted – first to assess the feasibility of this proposal, and then to further use complexity theory to deepen the understanding of the missio Dei.